Employee Attendance System with Facial Recognition Technology Using a Single Shot Detector (SSD) Algorithm - Djohari, Riyandi Dwitama; Ngemba, Hajra Rasmita; Hendra, Syaiful; Angraeni, Dwi Shinta; Lapatta, Nouval Trezandy; Nugraha, Deny Wiria (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
The attendance system is an important thing that is used to assess employee performance. Currently, many companies or organizations have developed attendance systems, but there are still many organizations that have not optimized attendance with a reliable system. This happens at the Palu City Tourism Office, where attendance still uses manual recording in album books. Many problems occur with the manual attendance process, so it is necessary to create an attendance system. This research aims to help the Palu City Tourism Office for attendance management by using face recognition technology using the Single Shot Detector (SSD) algorithm. The system development model uses Waterfall. This research uses 20 different facial poses with four people each with 5 poses. This research uses javascript programming language, Next JS framework, tailwind CSS, PostgreSQL database, and face-api.js library. Tests carried out with blackbox results all features on the system function properly then based on the results of face detection testing, the test results obtained that the Single Shot Detector algorithm can detect facial images recorded on the camera quickly and accurately in medium and bright lighting with a distance of 40-80 cm.  The result of this research is a system that can recognize faces well by matching the training data image with the face image recorded on the camera in realtime